ANALISIS PERLINDUNGAN HUKUM DAN TANGGUNG JAWAB PERDATA BANK TERHADAP NASABAH KORBAN PHISHING BERDASARKAN UNDANG-UNDANG NO. 8 TAHUN 1999 - Mohamad Sabiq Mohamad Nur; Dara Pustika Sukma (Sebelas Maret University, 2025)
The background of this research is related to the increase in the use of electronic banking services in line with the increasing threat of cybercrime, especially phishing, which results in financial losses for customers and damages public trust in the digital banking system. This research aims to analyze legal protection for customers and bank civil liability, as well as identify legal remedies that can be accessed by customers who are victims of phishing based on Law Number 8 of 1999 concerning Consumer Protection. The method used is normative legal research with a regulatory and conceptual approach. The results of the study show that banks have legal obligations related to system and data security guarantees, in accordance with the Financial Services Authority (OJK) Regulation and related laws. The bank's civil liability can be enforced if it is proven that there is negligence in carrying out these obligations. Customers who are victims of phishing have legal options, including criminal reporting and civil litigation, but the Consumer Protection Law provides a more structured dispute resolution path through internal complaints and SJK LAPS. In conclusion, despite the existence of a legal framework, customer protection depends on proving and optimizing dispute resolution mechanisms.